Application of cellulose nanowhisker and lignin in preparation of rigid polyurethane nanocomposite foams - Li, Yang (Georgia Institute of Technology, 2012)
Cellulose nanowhisker (CNW) prepared by acid hydrolysis of softwood Kraft pulp was incorporated as nanofiller in rigid polyurethane (PU) foam synthesis. The density, morphology, chemical structure, mechanical properties and thermal behavior of the products were characterized. The nanocomposites exhibited better performance especially at high CNW¡¯s content which was probably due to the high specific strength and aspect ratio of CNW, the hydrogen bonding and crosslinking between CNW and polymer matrix, a higher crosslinking density compared to the control, and the function of CNW as an insulator and mass transfer insulator. Lignin polyol was synthesized through oxypropylation and used for rigid PU foam preparation. The density, morphology, chemical structure, compressive property and thermal behavior of the product were characterized. Lingin-based rigid PU foam showed improved compressive property compared to its commercial counterpart. Ethanol organosolv lignin-based PU showed a slightly stronger compressive property than Kraft lignin-based PU. The enhancement was primarily attributed to the rigid phenolic structure and the high hydroxyl functionality of lignin. Lignin-based PU generated more char than common PUs which was possibly related to the better flame retardant property. This study provided an alternative way to valorize the two most abundant biopolymers and resulted in relatively environmentally benign rigid PU nanocomposite foam.